SLANG EXPRESSION IN LITTLE MAN MOVIE BASED ON SOCIAL DIMENSION - Wiruma Titian Adi; Alfian Azmi (Center of Language and Cultural Studies, 2018)
This research aims to reveal the slang expression (slang words) uttered by some characters in Little Man movie. To analyze them, the writers use Holmes’ references about social scale which is classified into four scales. By using qualitative descriptive method, the writers found 18 slang words then analyzed them into social distance scale, status scale, formality scale, or functional scale. After classifying these scales, it can be concluded that social distance scale is the mostly used in the movie. It can be assumed that social distance scale has told about the relationship between characters.